(a - b)^3(a−b)3
(a - b)^3 = (a - b) (a - b) (a - b)(a−b)3=(a−b)(a−b)(a−b)
(a - b)^3 = (a - b) [(a - b) (a - b)](a−b)3=(a−b)[(a−b)(a−b)]
(a - b)^3 = (a - b) [a^2 -ab -ab + b^2](a−b)3=(a−b)[a2−ab−ab+b2]
(a - b)^3 = (a - b) [a^2 -2ab + b^2](a−b)3=(a−b)[a2−2ab+b2]
(a - b)^3 = a (a^2 -2ab + b^2) - b (a^2 -2ab + b^2)(a−b)3=a(a2−2ab+b2)−b(a2−2ab+b2)
(a - b)^3 = a^3 -2a^2b + ab^2 - a^2b + 2ab^2 - b^3(a−b)3=a3−2a2b+ab2−a2b+2ab2−b3
(a - b)^3 = (a^3 - b^3) + (- 2a^2b - a^2b) + (ab^2 + 2ab^2)(a−b)3=(a3−b3)+(−2a2b−a2b)+(ab2+2ab2)
(a - b)^3 = (a^3 - b^3) + (- 3a^2b) + (3ab^2)(a−b)3=(a3−b3)+(−3a2b)+(3ab2)
(a - b)^3 = a^3 - b^3 - 3a^2b + 3ab^2(a−b)3=a3−b3−3a2b+3ab2